PENGARUH PENDEKATAN GROWTH MINDSET UNTUK MENGATASI KETAHANAN DAN KARAKTER BELAJAR SISWA KELAS V SDN 15 KOTO BESAR - devina dwi gosling; ajeng gusrinda (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2026)
This study aims to determine the effect of the growth mindset approach in addressing learning resilience and developing learning character in fifth-grade students at SDN 15 Koto Besar. The growth mindset approach emphasizes that abilities and intelligence can develop through effort, practice, and a persistent attitude. The research method used was quantitative research with an experimental design. The subjects were 17 fifth-grade students at SDN 15 Koto Besar. Data collection techniques included observation, questionnaires, and documentation. The data were analyzed using statistical tests to determine the effect of the growth mindset approach on students' learning resilience and learning character. The results showed that implementing the growth mindset approach had a positive impact on students' learning resilience, such as increased enthusiasm for learning, the ability to overcome difficulties, and a persistent attitude. Furthermore, this approach also influenced the development of students' learning character traits, such as discipline, responsibility, self-confidence, and hard work. Thus, the growth mindset approach can be an effective learning strategy in improving the quality of learning resilience and learning character in elementary school students. Keyword : growth mindset, resilience, character, students.